KARAKTERISTIK DAN FRAGMEN SEJARAH MANUSKRIP MUSHAF ALQURAN DOLAH BAKRI BANTUL - Yahya, Mohamad; Aini, Adrika Fithrotul (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2017)
This research aims to elaborate the characteristics of the Qur?anic manuscript of Dolah Bakri (MADB) by using philology and historical analysis. In its chronicle history, it shows that MADB appeared in Wonolelo in the 19th century. The use of paper, the technique of writing, the layout and illumination show its character as a mushaf born with the nuances of Javanese locality. In addition, when his contemporaries used mixed rasm, ?Uthma}ni} and imla}?i}, MADB consistently used the rasm ?uthma}ni}. From the social context, in Wonolelo, MADB was not merely as a Qur?anic mushaf which is used as a medium of reading for local Muslim community, but it had social and economic function as well. MADB could be a symbol of an economic power of its owner. MADB could also be a symbol of the integration of Islamic movement and social class identity of economic society.